Between duplication of existing patterns and onymic inventiveness: pragmatic-functional use of names in marketing - Siwiec, Adam (Papers in Linguistics, 2022)
The article is concerned with two contradictory tendencies in naming objects associated with consumption, i.e., in proper names with marketing application. The first tendency is to introduce names coined according to a pattern (a model series) and a variety of semiotic conventions. The other one is to strive for uniqueness, originality and onymic inventiveness. The latter is especially common in names used as messages and marketing slogans. Their advertising function is coupled with the desire to render them more attractive and attention-gripping based on their linguistic shape.